Peranan Aplikasi Android Dalam Peningkatan Kualitas Pelayanan Sekolah di Pesantren Persis Kota Tasikmalaya - Fadhlillah Fadhlillah; Aos Kuswandi; Pauzan Haryono (Kelola: Jurnal Manajemen Pendidikan, 2021)
The goals of this research are 1) to find out school services that are implemented in Pesantren PERSIS Benda Kota Tasikmalaya, 2) to get an overview of the android application used in pesantren PERSIS Benda Kota Tasikmalaya. 3) to measure the role of “67Benda” android applications in improving school services to student’s parents. This research is a qualitative research that produces data in the form of descriptions. Data collection methods using observation, interviews ang document study. The results shows that pesantren PERSIS Benda Kota Tasikmalaya gradually improve the quality of ducation because the role of the ‘67Benda” android application that has been implemented. It has been running well even thought the system and service need to be improved. There are some things are needed to support the use of this application such as, the qualified and adequate operators, a proper infrastructure, and the support also enthusiasm from teachers and parents. Factors that may hinder the use of “67Benda” are: (1) unskilled human resources in managing the application, (2) the incomplete application, and (3) signal interference. The role of the implementation “67Benda” android application has shown a very significant outcome to school services. It can be seen that the information is easier to be obtained by the student’s parents.